Three dimensional cell reconstructions for morphological analysis and modelling - Ratcliffe, Jonathan Albert (2011)
It is highly desirable to devise a systematic approach to predict cell – material interactions, especially for novel biomaterial surfaces, and to further understanding in the complex area of attachment and spreading. The aim of this research was to produce a new method of studying morphology in real time, whereby data from live spreading cells can be collected for mathematical modelling. There is an abundance of models for sub-cellular elements, however, there are few calibrated models of whole cells; in particular, three-dimensional models predicting attachment, spreading and cell morphology have yet to be produced.